Verb Movement and Expletive Subjects in the Germanic Languages. - Vikner, Sten (Oxford studies in comparative syntax., 1995)
This book is the study of two different kinds of variation across the Germanic languages. One involves the position of the finite verb, and the other the possible positions of the ""logical"" subject in constructions with expletive (or ""dummy"") subjects. The book applies the theory of Principles-and-Parameters to the study of comparative syntax. Several languages are considered, including less frequently discussed ones like Danish, Faroese, Icelandic, and Yiddish.